Konsep Diri dan Online Disinhibition Effect Pada Dewasa Awal di Banda Aceh - Suri Akyun; Kartika Sari; Afriani Afriani; Arum Sulistyani (Syiah Kuala Psychology Journal, 2025)
Internet has changed the way individuals communicate with others, so that individuals tend to have the freedom to express everything in cyberspace including expressing bad comments or hate speech on social media. The online disinhibition effect was found to be associated with aggressive and deviant behavior carried out online. One of the factors that influences the online disinhibition effect in early adulthood is self-concept. This research aims to determine the relationship between self-concept and the online disinhibition effect in early adulthood in Banda Aceh. A total of 303 early adults in Banda Aceh were selected based on the criteria of being 20-40 years old, using a smartphone or computer, accessing the internet and using social media and domiciled in Banda Aceh. This research uses a convenience sampling sample selection technique. Data collection using the Online Disinhibition Scale (ODS) and Personal Self-Concept Questionnaire (PSQ). The results of the hypothesis test show a correlation coefficient value of (r)=-0.145 and a significance value of (p)=0.016 (p0.05) meaning that there is a negative relationship between self-concept and the online disinhibition effect in early adulthood in Banda Aceh, which means that the higher the self-concept in early adulthood in Banda Aceh, the lower the online disinhibition effect, and vice versa.Internet telah mengubah cara individu berkomunikasi dengan orang lain, sehingga individu cenderung leluasa untuk mengekspresikan segala hal di dunia maya termasuk mengungkapkan komentar buruk atau ujaran kebencian di media sosial. Online disinhibition effect ditemukan berhubungan dengan perilaku agresif dan menyimpang yang dilakukan secara daring. Salah satu faktor yang memengaruhi online disinhibition effect pada dewasa awal adalah konsep diri. Penelitian ini bertujuan untuk mengetahui hubungan konsep diri dengan online disinhibition effect pada dewasa awal di Banda Aceh. Sebanyak 303 dewasa awal di Banda Aceh dipilih dengan kriteria berusia 20-40 tahun, menggunakan ponsel pintar atau komputer, mengakses internet dan menggunakan sosial media serta berdomisili di Banda Aceh. Penelitian ini menggunakan teknik pemilihan sampel convenience sampling. Pengumpulan data menggunakan Online Disinhibition Scale (ODS) dan Personal Self-Concept Questionnaire (PSQ). Hasil analisis menunjukkan nilai korelasi (r)=-0.145 dan nilai signifikansi (p)=0.016 (p0,05) artinya terdapat hubungan yang negatif antara konsep diri dengan online disinhibition effect pada dewasa awal di Banda Aceh, yang artinya bahwa semakin tinggi konsep diri pada dewasa awal di Banda Aceh maka semakin rendah online disinhibition effect, begitu pula sebaliknya.